DNA transposon invasion and microsatellite accumulation guide W chromosome differentiation in a Neotropical fish genome - Schemberger, Michelle Orane; Nascimento, Viviane Demetrio; Coan, Rafael [UNESP]; Ramos, Erica [UNESP]; Nogaroto, Viviane; Ziemniczak, Kaline; Valente, Guilherme Targino [UNESP]; Moreira-Filho, Orlando; Martins, Cesar [UNESP]; Vicari, Marcelo Ricardo (Springer, 2019)
Sex chromosome differentiation is subject to independent evolutionary processes among different lineages. The accumulation of repetitive DNAs and consequent crossing-over restriction guide the origin of the heteromorphic sex chromosome region. Several Neotropical fish species have emerged as interesting models for understanding evolution and genome diversity, although knowledge of their genomes is scarce. Here, we investigate the content of repetitive DNAs between males and females of Apareiodon sp. based on large-scale genomic data focusing on W sex chromosome differentiation. In Apareiodon, females are the heterogametic sex (ZW) and males are the homogametic sex (ZZ). The genome size estimate for Apareiodon was 1.2 Gb (with similar to 42x and similar to 47x coverage for males and females, respectively). In Apareiodon sp., approximately 36% of the genome was composed of repetitive DNAs and transposable elements (TEs) were the most abundant class. Read coverage analysis revealed different amounts of repetitive DNAs in males and females. The female-enriched clusters were located on the W sex chromosome and were mostly composed of microsatellite expansions and DNA transposons. Landscape analysis of TE contents demonstrated two major waves of invasions of TEs in the Apareiodon genome. Estimation of TE insertion times correlated with in situ locations permitted the inference that helitron, Tc1-mariner, and CMC EnSpm DNA transposons accumulated repeated copies during W chromosome differentiation between 20 and 12 million years ago. DNA transposons and microsatellite expansions appeared to be major players in W chromosome differentiation and to guide modifications in the genome content of the heteromorphic sex chromosomes.
Keywords: Cytogenomics; Read coverage analysis; Sex chromosomes; Tandem repeats; Transposable elements; W chromosome region